The Democratic Peace Unraveled: Its the Economy - Michael Mousseau (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
Recent research indicates that the democratic peace - the observation that democratic nations rarely fight each other - is spurious: that advanced capitalism accounts for both democracy and the democratic peace (Mousseau 2009). This is not a trivial prospect: if economic conditions explain the democratic peace, then a great deal of research on governing institutions and foreign policy is probably obsolete. This study addresses all the recent defenses of the democratic peace and reports new results using a new measure that directly gauges the causal mechanism of contract flows dependent on third-party enforcement. Analyses of most nations from 1961 to 2001 show contract-intensive "impersonal" economy to be the second most powerful variable in international conflict - following only contiguity - and, once considered, there is no evidence of causation from democracy to peace. It is impersonal economy, not democracy or unfettered markets, which appears to explain the democratic peace.
Keywords: 330; Politischer Konflikt; Außenwirtschaftspolitik; Demokratie; Systemvergleich; Welt